2000
DOI: 10.1093/brain/123.7.1380
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral caudate and putamen grafts of embryonic mesencephalic tissue treated with lazaroids in Parkinson's disease

Abstract: Five parkinsonian patients were transplanted bilaterally into the putamen and caudate nucleus with human embryonic mesencephalic tissue from between seven and nine donors. To increase graft survival, the lipid peroxidation inhibitor tirilazad mesylate was administered to the tissue before implantation and intravenously to the patients for 3 days thereafter. During the second postoperative year, the mean daily L-dopa dose was reduced by 54% and the UPDRS (Unified Parkinson's Disease Rating Scale) motor score in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
180
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 282 publications
(182 citation statements)
references
References 50 publications
2
180
0
Order By: Relevance
“…The lazaroids, a group of compounds which have been developed for acute treatment of CNS injury, have been confirmed to improve the survival of grafted embryonic dopaminergic neurons by animal experiments [34] . Brundin and his colleagues found when tirilazad mesylate was administered to mesencephalic tissue prior to implantation and intravenously to patient for 3 d after surgery, the patients experienced the same improvement on functional performance and striatal [ 18 F] fluorodopa uptake as the previous patients who were implanted with twice much mesencephalic tissue [35] .…”
Section: Antioxidants and Antiapoptotic Agentsmentioning
confidence: 91%
“…The lazaroids, a group of compounds which have been developed for acute treatment of CNS injury, have been confirmed to improve the survival of grafted embryonic dopaminergic neurons by animal experiments [34] . Brundin and his colleagues found when tirilazad mesylate was administered to mesencephalic tissue prior to implantation and intravenously to patient for 3 d after surgery, the patients experienced the same improvement on functional performance and striatal [ 18 F] fluorodopa uptake as the previous patients who were implanted with twice much mesencephalic tissue [35] .…”
Section: Antioxidants and Antiapoptotic Agentsmentioning
confidence: 91%
“…Similar to the time course of improvement in the open-label trials, grafted patients showed progressive symptomatic relief during the first 6 to 9 months after surgery, but then reverted back to baseline. The lack of efficacy could be explained by the patients of Olanow et al [14] being more severely disabled as compared to those, for example, in the Swedish series [4,8,18]. In support of this idea, Olanow et al [14] found significant improvement in their less severely disabled patients compared to the sham group at 2 years.…”
Section: Can Da Neurons Be Replaced and Neural Grafts Have Functionalmentioning
confidence: 97%
“…Neither in the open-label nor in the sham-surgery controlled clinical trials, improvements after intrastriatal transplantation of fetal mesencephalic DA-rich tissue in PD patients [4,6,8,9,13,14] have exceeded those found with DBS in the subthalamic nucleus [80]. Moreover, there is no Fig.…”
Section: Toward An Effective and Safe Cell Therapy For Pdmentioning
confidence: 98%
See 2 more Smart Citations